2005
DOI: 10.1584/jpestics.30.354
|View full text |Cite
|
Sign up to set email alerts
|

Flubendiamide, a Novel Insecticide Highly Active against Lepidopterous Insect Pests

Abstract: Flubendiamide, N2 -[1,1-dimethyl-2-(methylsulfonyl)ethyl]-3-iodo-N 1 -[2-methyl-4-[1,2,2,2-tetrafluoro-1-(trifluoromethyl)ethyl]phenyl]-1,2-benzenedicarboxamide, is a novel class of insecticide having a unique chemical structure. The uniqueness of the structure results from three parts with novel substituents; a heptafluoroisopropyl group in the anilide moiety, a sulfonylalkyl group in the aliphatic amide moiety, and an iodine atom at the 3-position of the phthalic acid moiety. The compound shows extremely str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
185
0
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 325 publications
(215 citation statements)
references
References 8 publications
6
185
0
11
Order By: Relevance
“…The leaf-dipping bioassay method using Brassica rapa L. leaves was applied. 3) In each bioassay, 5-7 concentrations of flubendiamide (0.02-2000 mg/L) and of chlorantraniliprole (0.005-500 mg/L) were tested. After 96 hr, the numbers of dead or moribund larvae and surviving larvae were recorded.…”
Section: Bioassaymentioning
confidence: 99%
“…The leaf-dipping bioassay method using Brassica rapa L. leaves was applied. 3) In each bioassay, 5-7 concentrations of flubendiamide (0.02-2000 mg/L) and of chlorantraniliprole (0.005-500 mg/L) were tested. After 96 hr, the numbers of dead or moribund larvae and surviving larvae were recorded.…”
Section: Bioassaymentioning
confidence: 99%
“…3,4) Meanwhile, a novel insecticide 2 with a unique heptafluoroisopropyl substituent was reported by our colleague. 5,6) We initially designed and synthesized a hybrid analogue 3 with substituents characteristic in such fungicides and insecticides together, but it showed only low fungicidal activity. It seemed that this low fungicidal activity was attributed to the high lipophilicity of derivative 3.…”
Section: Introductionmentioning
confidence: 99%
“…The yield loss caused by this pest is enormous and varies from 37% to 63% in different parts of India (Dhankar, 1988), up to 67% every year in Bangladesh (Islam & Karim, 1991). Latif, 2007 reported that Nimbicidene and Flubebdiamite were comparatively safe for natural enemies and insect pest management of brinjal on the other hand, Tohnishi et al (2005) reported that flubendiamide was highly toxic to Lepidopteran insect pests but it was very safe for different natural enemies like ladybird beetles, spiders, parasitic wasp, lacewings, predatory bug and predatory mite.…”
Section: Introductionmentioning
confidence: 99%